Low Irradiation Concentrator Effects On The Photovoltaic Panels Performance - Rosde, Muhamad Zul Fadhli (Universiti Sains Malaysia, 2017)
Photovoltaic cells have been one of the most used and convenient power generations in the urbanisation world where nowadays the resources that have been used as power generations is coming to an era where it will dried out and desolated. One of the objectives of this project is to make improvement to the existing power generations at home to get a higher efficiency of the solar panels by installing concentrators to its’ systems. The other objective of the project is to investigate the best solar panels in the market nowadays. By investigating which one is the best among the popular solar panels and the effects of concentrator on photovoltaic panels, it can ease the purchasing and installation of the best systems at home. In the project, data of current, voltage, temperature and light luminance are measured and recorded. Tabulating and presenting the data in tables and also I-V and P-V curves can ease the conclusion making. The final results show that HIT is the desirable among all other 4 solar panels and the concentrators does have effects on the solar panels performance.